If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 59 + 44t = 19t + -39 Reorder the terms: 59 + 44t = -39 + 19t Solving 59 + 44t = -39 + 19t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-19t' to each side of the equation. 59 + 44t + -19t = -39 + 19t + -19t Combine like terms: 44t + -19t = 25t 59 + 25t = -39 + 19t + -19t Combine like terms: 19t + -19t = 0 59 + 25t = -39 + 0 59 + 25t = -39 Add '-59' to each side of the equation. 59 + -59 + 25t = -39 + -59 Combine like terms: 59 + -59 = 0 0 + 25t = -39 + -59 25t = -39 + -59 Combine like terms: -39 + -59 = -98 25t = -98 Divide each side by '25'. t = -3.92 Simplifying t = -3.92
| 3x+44=8x-6 | | 8y=3(y-5) | | 4x-5=9x-7 | | X^3-3x^2-104x+216=0 | | 2x+3=9x-7 | | 2(0)=3y-13 | | e^6x=55e^9x | | .59+.44t=1.9t-.39 | | 5c-4(c-9)=2+2c | | 5(-1)-2y=-19 | | 6r^2-9=-3r | | -(1-x)=2(4-x) | | 6x-22=8x-34 | | 0.6(x+-.0300)=0.65-0.01(x+1) | | 5*47.5+-0.5b+4b=269 | | 3m^2=12 | | 5y+2(4)=58 | | 3x+6=5+2x | | x=5x-45 | | 5h+4h+3= | | 9x-40+3x-30=180 | | 2(x^2+4)+5(x+2)-3=0 | | x+3=-1+2x | | x+13=19x | | -10+6y=25+y | | 6p^2-10=0 | | 9(-3)+5y=-33 | | 5-2(x+21)=12 | | 36-10m=2(m-2) | | 0=(5x+6)(x-9) | | 5xy+y=0 | | 9(x-3)-6=2(x+5)+13 |